Oxidative Stress Down-Regulates MiR-20b-5p, MiR-106a-5p and E2F1 Expression to Suppress the G1/S Transition of the Cell Cycle in Multipotent Stromal Cells - Tai, Lihui; Huang, Chiu Jung; Choo, Kong Bung; Cheong, Soon Keng; Kamarul, Tunku (Ivyspring International Publisher, 2020)
Oxidative stress has been linked to senescence and tumorigenesis via modulation of the cell cycle. Using a hydrogen peroxide (H2O2)-induced oxidative stress-induced premature senescence (OSIPS) model previously reported by our group, this study aimed to investigate the effects of oxidative stress on microRNA (miRNA) expression in relation to the G1-to-S-phase (G1/S) transition of the cell cycle and cell proliferation. On global miRNA analysis of the OSIPS cells, twelve significantly up-or down-regulated miRNAs were identified, the target genes of which are frequently associated with cancers. Four down-regulated miR-17 family miRNAs are predicted to target key pro-and anti-proliferative proteins of the p21/cyclin D-dependent kinase (CDK)/E2F1 pathway to modulate G1/S transition. Two miR-17 miRNAs, miR-20-5p and miR-106-5p, were confirmed to be rapidly and stably down-regulated under oxidative stress. While H2O2 treatment hampered G1/S transition and suppressed DNA synthesis, miR-20b-5p/miR-106a-5p over-expression rescued cells from growth arrest in promoting G1/S transition and DNA synthesis. Direct miR-20b-5p/miR-106a-5p regulation of p21, CCND1 and E2F1 was demonstrated by an inverse expression relationship in miRNA mimic-transfected cells. However, under oxidative stress, E2F1 expression was down-regulated, consistent with hampered G1/S transition and suppressed DNA synthesis and cell proliferation. To explain the observed E2F1 down-regulation under oxidative stress, a scheme is proposed which includes miR-20b-5p/miR-106a-5p-dependent regulation, miRNA-E2F1 autoregulatory feedback and E2F1 response to repair oxidative stress-induced DNA damages. The oxidative stress-modulated expression of miR-17 miRNAs and E2F1 may be used to develop strategies to retard or reverse MSC senescence in culture, or senescence in general. © The author(s).